Confusing presentation of chaetomium brain abscess. (December 2014) - Waqas, Muhammad; Waheed, Shahan; Mangrio, Salman Ahmed; Rashid, Sana; Qadeer, Mohsin; Bari, Ehsan
Abstract We put forth the case of a young immunocompetent female who presented with fever and left basal ganglia bleed secondary to vasculitis. After 2 weeks of prednisolone therapy, she continued to deteriorate. MRI scan revealed enhancement of previous hematoma, pus was aspirated surgically and fungal culture grew Chaetomium.